IMPLEMENTATION OF THE LITERACY MOVEMENT IN SOCIETY - Prihatin, Yulianah (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The low interest in reading in Indonesia requires educational institutions to create innovations to help increase people's interest in reading. In 2011, based on data from the World’s Most Literate Nations, Indonesia was in 60th place regarding the reading interest of its population. The order is classified as low compared to other countries. Currently, the government has created the National Literacy Movement as an effort to increase the percentage of people's reading interest. However, it needs to be supported by many parties. Based on this, the KKNT team in the village of Marmoyo made an innovation to establish a Smart House so that people love reading more, especially reading fairy tales to their children. Fairy tales are a form of folklore that develops both orally and in writing. Regions in Indonesia have thousands of fairy tales that deserve to be preserved, this is because the younger generation knows and knows the developing fairy tales. In addition, the activity of reading fairy tales to children (ndongeng) is proven to be able to instill character and create closeness between parents and children. The method for this service is carried out by analyzing partner situations, reviewing literature / references related to the PKM theme, implementing fairy tale reading training with an interesting method in the village of Marmoyo for two days, cultivating reading fairy tales through a smart house. The fairy tale reading training program and the application of the Smart House in the village of Marmoyo are proven to be able to change the people's mindset about the benefits of fairy tales, and make it easier for people to find reading material.